Daylight modelling and thermal performance of atrium of new MECM building at Putrajaya - Fuziah, Sulaiman; Azni, Zain Ahmed, Prof. Dr.; Shuzlina, Abdul Rahman; Adizul, Ahmad (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/